Standardization of coconut (Cocos Nucifera Linn.) oil refining for village level production - Velasquez, Esther de la Merced
This research on the standardization of coconut oil refining was conducted to generate a simple method of processing that could be utilized by small coconut farmer cooperatives. The factors for refining which were given consideration were temperature (80°C and 90°C), use of alkali (1% NaOH) and aqueous solutions and application or non-application of stirring. Characterization of crude and refined oil samples were done thrice. The physico-chemical analysis conducted comprised of free fatty acid (FFA), color, moisture, pH and peroxide value (PV) determination. Results were compared to the standard values. Results for FFA and color of crude oil met the standard but the moisture exceeded the standard by 0.37%. The refined coconut oil samples met the standard color and PV except for one. For the FFA analysis, only those treated with NaOH passed the standard. Results of the sensory evaluation and analysis using three-way ANOVA with interaction and DMRT showed significant effects due to the use of alkali and aqueous solutions. The other factors namely: temperature and application or non-application of stirring showed insignificant effects. Panelists favored the coconut oil samples treated with NaOH in terms of odor, odor acceptability, color, color acceptability, rank and general acceptability. It is concluded that the best treatment combination for refining was the use of NaOH at 90°C without stirring.